2013
DOI: 10.1097/sla.0b013e3182a4e85a
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcome of Local Excision versus Radical Resection of Colon or Rectal Carcinoma

Abstract: Local excision for early colorectal cancer was oncologically equivalent to major surgery for carcinoma in situ and T1 rectal cancer, but inferior for T1-2 colon and T2 rectal cancer. Exploratory data suggest local excision of T1-2 rectal cancer after neoadjuvant therapy may be safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…20 and Bhangu et al. 21 conducted two retrospective studies focusing on local excision versus radical resection for colorectal cancer in all ages based on SEER database. The former one suggested that local excision was associated with inferior CSS of T1 rectal cancer compared with radical resection.…”
Section: Discussionmentioning
confidence: 99%
“…20 and Bhangu et al. 21 conducted two retrospective studies focusing on local excision versus radical resection for colorectal cancer in all ages based on SEER database. The former one suggested that local excision was associated with inferior CSS of T1 rectal cancer compared with radical resection.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, administered CRT in all patients with pT1 rectal cancer postoperatively. Some studies have found no difference between local excision and TME surgery in local recurrence rates or outcomes of patients with T1 rectal cancer [7, 14, 29]. However, Stornes et al [6] studied 543 patients with T1 rectal cancer and reported that the local recurrence rate was 14.5% in patients who underwent transanal endoscopic microsurgery, which was significantly higher than the recurrence rate (1.4%) in patients who underwent TME ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence is limited and well-designed clinical trials are required for cT1, sm1 tumors with low-risk features, standard transanal excision or excision by means of TEM, if technically feasible, is recommended as definitive treatment [ 154 , 155 ]. For cT1, sm2 tumors with low-risk features definitive treatment (TME) is the treatment of choice.…”
Section: Transabdominal Resection: Surgical Principlesmentioning
confidence: 99%
“…For cT1, sm2 tumors with low-risk features definitive treatment (TME) is the treatment of choice. Local excision is not recommended outside clinical trials, unless the patient refuses definitive treatment or has co-morbidities [ 154 , 155 ]. If histopathology shows deeper invasion or additional high-risk features (poor differentiation, lympho-vascular, venous or neural invasion) CRT can be added with or without definitive surgery.…”
Section: Transabdominal Resection: Surgical Principlesmentioning
confidence: 99%